Answers

2014-08-21T20:44:11+05:30
 \frac{x}{ \sqrt{ x^{2}-1}}+ \frac{ x^{2}-1 }{x} = \frac{ x^{2} +( \sqrt{ x^{2} -1})( x^{2} -1) }{x( \sqrt{ x^{2} -1)} } = \frac{ x^{2} +( x^{2} -1)( \sqrt{x^2-1}) }{x( \sqrt{x^2-1}) }=[tex] \frac{ x^{2} + x^{2} ( \sqrt{x^2-1})- 1( \sqrt{x^2-1)} }{x( \sqrt{x^2-1}) } =[tex] \frac{ x^{2} }{x( \sqrt{x^2-1}) } + \frac{x^2( \sqrt{x^2-1}) }{x( \sqrt{x^2-1}) } - \frac{ \sqrt{x^2-1} }{x( \sqrt{x^2-1}) }= \frac{x}{ \sqrt{x^2-1} } +x-1= \frac{2x-1}{ \sqrt{x^2-1} } = \frac{2x-1( \sqrt{x^2+1)} }{ (\sqrt{x^2-1)-( \sqrt{x^2+1)} } }
0